Preparation method of nano reinforced and toughened ultraviolet-resistant plastic material
Through the nano-enhanced preparation method, combined with modified biopolyester, modified cellulose and composite nanoparticles, the shortcomings of existing automotive plastic shell materials in terms of mechanical, antistatic, ultraviolet resistance and degradation properties are solved, and high-performance and environmentally friendly plastic material preparation is achieved.
Patent Information
- Application Number
- CN202510143720.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-10
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing automotive plastic shell materials cannot fully meet the high requirements of the new energy vehicle industry in terms of mechanical properties, antistatic properties, ultraviolet resistance and degradation properties.
Using a nano-enhanced preparation method, melt extrusion and granulation are carried out through the combination of modified biopolyester, modified cellulose, composite nanoparticles and diapropylene peroxide to form plastic materials with toughening and ultraviolet resistance.
It significantly improves the toughness, strength and antistatic properties of plastic materials, while enhancing its environmental protection performance, and maintains stable performance under external forces and ultraviolet rays.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of plastic material processing, and in particular to a method for preparing a nano-reinforced and toughened ultraviolet-resistant plastic material. Background Art
[0002] The arrival of the new energy era has brought new opportunities for the development of my country's automobile industry. The application of new energy technology in vehicle engineering is conducive to reducing the degree of environmental pollution caused by the automobile production process, making it more in line with the concept of low-carbon economic development. In order to further reduce the energy consumption of new energy vehicles, some manufacturers are gradually using plastic materials to replace the metal materials used in the automobile production process, so as to reduce the weight of the car, alleviate the high-frequency use of non-renewable energy, and provide certain impetus for the further development of the new energy vehicle field.
[0003] In the design of automobile plastic shells, the strength, toughness, UV resistance and environmental protection of the materials are key factors. In the existing technology, the commonly used plastic materials for manufacturing new energy vehicle shells are polypropylene, polystyrene, polyvinyl chloride, etc. Although these plastics have the advantages of light weight and strong plasticity, during use, the arrangement of their molecular chains lacks sufficient cross-linking structure, resulting in weak tensile strength and impact resistance, and easy to break or deform. Secondly, in a low temperature environment, the molecular chain of the plastic material is relatively rigid, lacks sufficient flexibility, and is easy to become brittle and break. Moreover, long-term exposure to sunlight will break the molecular chain due to ultraviolet rays, causing the plastic to age, fade and deteriorate in performance. The non-degradability also makes it difficult to recycle or dispose of the shells packaged in these plastic materials after they are discarded, and may release toxic gases, which will burden the environment.
[0004] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a nano-reinforced and toughened UV-resistant plastic material, which is used to solve the technical problem that the plastic materials in the prior art cannot fully meet the high requirements of the new energy vehicle industry for plastic materials in terms of mechanical properties, antistatic properties, UV resistance and degradation properties.
[0006] The object of the present invention can be achieved by the following technical scheme: A method for preparing a nano-reinforced and toughened ultraviolet-resistant plastic material comprises the following steps:
[0007] S1. Place itaconic acid, sebacic acid, toluene, boron trifluoride and 1,4-butanediol in a three-necked flask, heat to 120-130° C., keep warm for 4-6 hours, and post-treat to obtain unsaturated polyester;
[0008] The synthesis reaction principle of unsaturated polyester is:
[0009] The terminal carboxyl groups on the molecular chains of sebacic acid and itaconic acid react with the terminal hydroxyl groups of 1,4-butanediol to form unsaturated polyester.
[0010] S2, placing unsaturated polyester, toluene and toluene diisocyanate in a three-necked flask, heating to 75-85° C., keeping the temperature for reaction for 2-3 hours, and post-treating to obtain modified bio-polyester;
[0011] The synthetic reaction equation of modified biopolyester is:
[0012] ;
[0013] ;
[0014] Where:
[0015] ;
[0016] The synthetic reaction principle of modified biopolyester is:
[0017] The two isocyanate groups contained in the toluene diisocyanate molecule can react with the hydroxyl groups on the unsaturated polyester chain segment to extend the length of the polymer chain. By controlling the excessive use of toluene diisocyanate, a modified bio-polyester terminated with toluene diisocyanate groups is formed.
[0018] S3, adding the modified bio-polyester, modified cellulose, composite nanoparticles, dicumyl peroxide and auxiliary additives into a twin-screw extruder for melt extrusion, and then injecting into a single-screw granulator to obtain a plastic material.
[0019] Furthermore, in step S1, the dosage ratio of itaconic acid, sebacic acid, toluene, boron trifluoride and 1,4-butanediol is 100-200g:150-320g:5-10L:5g:300-400g, and the post-treatment step includes: after the reaction is completed, adding purified water to the three-necked flask, raising the temperature of the reactor to 120-130°C, and distilling under reduced pressure until no liquid is produced to obtain unsaturated polyester; in step S2, the dosage ratio of the unsaturated polyester and toluene is 50-100g:1-1.5L, the molar ratio of toluene diisocyanate is half of the molar amount of hydroxyl groups in the unsaturated polyester, and the post-treatment step includes: after the reaction is completed, the three-necked flask is cooled to room temperature, filtered, and the filter cake is transferred to a vacuum drying oven at a temperature of 65-75°C, and dried to constant weight to obtain modified bio-polyester.
[0020] Furthermore, in step S3, the auxiliary additives are composed of dispersant, antioxidant, and plasticizer in a weight ratio of 2:1:4, the dispersant is stearate, the antioxidant is one or more of antioxidant 168, antioxidant 364, and antioxidant 1010, the plasticizer is phthalate, the amount ratio of the modified bio-polyester, modified cellulose, composite nanoparticles, diisopropyl peroxide and auxiliary additives is 900-1000g:100-150g:150-200g:10-15g:50-80g, the temperatures of the eight temperature zones of the twin-screw extruder from the feed end to the discharge end are 200°C, 210°C, 210°C, 215°C, 215°C, 215°C, 215°C, and 220°C, respectively, and the spindle speed of the twin-screw extruder is 18r / min.
[0021] Furthermore, the preparation method of the modified cellulose comprises the following steps:
[0022] A1. Under the protection of inert gas, hydroxyethyl cellulose, tetrahydrofuran, pyridine, acryloyl chloride and stearoyl chloride are placed in a three-necked flask, the temperature is raised to 50-60°C, the temperature is kept for reaction for 2-3 hours, and the esterified cellulose is obtained by post-treatment;
[0023] The synthetic reaction principle of esterified cellulose is:
[0024] Pyridine, as a catalyst, enhances the nucleophilicity of the hydroxyl groups in hydroxyethyl cellulose through deprotonation. The protonated hydroxyl groups attack the acyl chloride carbon atoms of acryloyl chloride and stearoyl chloride, resulting in esterification reaction to obtain esterified cellulose.
[0025] A2. Under nitrogen atmosphere, esterified cellulose, potassium persulfate and deionized water are placed in a three-necked flask, heated to 80-100° C., 2-methylene-1,3-dioxepane and methyl acrylate are added dropwise, and modified cellulose is obtained by post-treatment.
[0026] The synthetic reaction principle of modified cellulose is:
[0027] Under the initiation of potassium persulfate, the dioxane structure in 2-methylene-1,3-dioxepane undergoes a ring-opening reaction and undergoes a polymerization reaction with methyl acrylate and the olefin of esterified cellulose. Since potassium persulfate is water-soluble, the generated free radicals have a high hydrophilicity and are easily attached to the surface of esterified cellulose particles. The added monomers are mainly polymerized on the surface of the colloid particles to obtain modified cellulose with a core-shell structure.
[0028] Furthermore, in step A1, the amount ratio of hydroxyethyl cellulose, tetrahydrofuran, pyridine, acryloyl chloride and stearoyl chloride is 100-150g:1.2-1.3L:10-15g:5-10g:5-10g, and the post-treatment step includes: after the reaction is completed, filtering, washing the filter cake with ethanol 1-2 times, placing it in a vacuum drying oven at a temperature of 45-55°C and drying it to constant weight to obtain esterified cellulose; in step A2, the amount ratio of esterified cellulose, potassium persulfate, deionized water, 2-methylene-1,3-dioxepane and methyl acrylate is 100-150g:20-30g:3-5L:180-200g:80-90g, and the post-treatment step includes: after the reaction is completed, transferring the reaction solution to a rotary evaporator with a water bath temperature of 65-75°C, and reducing pressure and rotary evaporating until no liquid is extracted to obtain modified cellulose.
[0029] Furthermore, the preparation method of the 2-methylene-1,3-dioxepane comprises the following steps:
[0030] B1. Under a nitrogen atmosphere, place chloroacetaldehyde dimethyl acetal, 1,4-butanediol and a catalyst in a three-necked flask, heat to 110-120°C, keep warm for 1-2h, and post-treat to obtain 2-chloromethyl-1,3-dioxepane;
[0031] The synthetic reaction formula of 2-chloromethyl-1,3-dioxepane is:
[0032] ;
[0033] The synthetic reaction principle of 2-chloromethyl-1,3-dioxepane is:
[0034] On the acidic cation exchange resin Dowex 50 H + Under the catalysis of the type, the two alcoholic hydroxyl groups of 1,4-butanediol respectively undergo nucleophilic attacks on the carbon positive atom of chloroacetaldehyde in chloroacetaldehyde dimethyl acetal to generate an intermediate, which removes two molecules of methanol to generate 2-chloromethyl-1,3-dioxepane;
[0035] The mass spectrum analysis data of 2-chloromethyl-1,3-dioxepane are: 150.07 (100.0%), 155.04 (32.0%), 151.08 (6.7%), 153.08 (2.2%).
[0036] B2. Place potassium tert-butoxide, tert-butanol and N,N-dimethylformamide in a three-necked flask, add 2-chloromethyl-1,3-dioxepane dropwise, raise the temperature to 80-115°C, keep the temperature for 6-7h, and post-treat to obtain 2-methylene-1,3-dioxepane.
[0037] The synthetic reaction formula of 2-methylene-1,3-dioxepane is:
[0038] ;
[0039] The synthetic reaction principle of 2-methylene-1,3-dioxepane is:
[0040] Under the catalytic action of the strong base potassium tert-butoxide, tert-butanol is deprotonated to generate a strongly nucleophilic tert-butoxide ion. The tert-butoxide ion attacks the chloromethyl group in 2-chloromethyl-1,3-dioxepane, undergoing a nucleophilic substitution reaction, replacing the chlorine atom with a tert-butyl group. The tert-butyl group further leaves to generate 2-methylene-1,3-dioxepane.
[0041] The mass spectrum analysis data of 2-methylene-1,3-dioxepane are: 114.04 (100.0%), 115.04 (6.7%).
[0042] Furthermore, in step B1, the catalyst is an acidic cation exchange resin Dowex 50 H+ type, the amount ratio of the chloroacetaldehyde dimethyl acetal, 1,4-butanediol and the catalyst is 100-120g:80-100g:1-2g, and the post-treatment step comprises: after the reaction is completed, suction filtration, placing the filtrate on a rotary evaporator at a temperature of 40-45°C, and vacuum distilling until no liquid is produced to obtain 2-chloromethyl-1,3-dioxepane; in step B2, the amount ratio of the potassium tert-butoxide, tert-butanol, N,N-dimethylformamide and 2-chloromethyl-1,3-dioxepane is 17-20g:13-15g:800-1000mL:25-30g, and the post-treatment step comprises: after the reaction is completed, adding ether to a three-necked flask, heating to 110-120°C, and vacuum distilling until no liquid is produced to obtain 2-methylene-1,3-dioxepane.
[0043] Furthermore, the method for preparing the composite nanoparticles comprises the following steps:
[0044] C1. Place deionized water, ethanol and concentrated hydrochloric acid in a three-necked flask and stir at room temperature for 20-30 minutes to obtain a mixed acid solution for later use;
[0045] C2, put n-butyl titanate, vinyl triethoxysilane and ethanol in a three-necked flask, mix them evenly, add the mixed acid solution dropwise, stir at room temperature for 20-30 minutes, and obtain a nano titanium dioxide sol solution for standby use;
[0046] The synthetic reaction principle of nano titanium dioxide sol solution is:
[0047] Under acidic conditions, n-butyl titanate and deionized water undergo hydrolysis reaction to generate n-butyl titanate hydrate, and the silyl group of vinyltriethoxysilane undergoes hydrolysis to generate silanol. Further, each n-butoxy group in n-butyl titanate combines with each hydroxyl group in titanate tetrahydroxide to condense to form a Ti-O-Ti bond, thereby obtaining a nano-titanium dioxide sol solution.
[0048] C3. Under vacuum environment, immerse the graphene aerogel in nano-titanium dioxide sol solution, let it stand for 1-2 hours, heat it to 50-60°C, keep it warm for 3-4 hours, and then post-treat it to obtain composite nanoparticles.
[0049] Furthermore, in step C1, the volume ratio of deionized water, ethanol and concentrated hydrochloric acid is 10-20:20-40:1-2; in step C2, the amount ratio of n-butyl titanate, vinyl triethoxysilane, ethanol and mixed acid solution is 10-20mL:5-10g:20-40mL:5-10mL; in step C3, the post-treatment step includes: after the reaction is completed, washing with deionized water for 1-2 times, drying, and microwave irradiation at a power of 800W for 1-2min to obtain composite nanoparticles.
[0050] Furthermore, the preparation method of the graphene aerogel is: placing graphene oxide, L-ascorbic acid and deionized water in a three-necked flask, heating to 50-60° C., ultrasonically dispersing for 2-3 hours, and post-treating to obtain the graphene aerogel.
[0051] The synthetic reaction principle of graphene aerogel is:
[0052] L-ascorbic acid reduces the carboxyl groups on the surface of graphene oxide through electron transfer. The reduced graphene sheets are overlapped and stacked to form graphene aerogel with the help of π-π interaction and enhanced hydrophobic effect.
[0053] Furthermore, the usage ratio of the graphene oxide, L-ascorbic acid and deionized water is 10-20g:15-30g:200-500mL, and the post-treatment step includes: after the dispersion is completed, the dispersion is placed in a vacuum drying oven at a temperature of 70-80°C and dried to constant weight to obtain graphene aerogel.
[0054] The present invention has the following beneficial effects:
[0055] 1. The nano-reinforced and toughened UV-resistant plastic material of the present invention is prepared by melt granulation using modified bio-polyester as a basic raw material, modified cellulose and composite nanoparticles as reinforcing materials, dicumyl peroxide as a free radical initiator, and dispersants, antioxidants, and plasticizers as auxiliary additives. Under the initiation of dicumyl peroxide, the olefin bonds of the modified cellulose and the composite nanoparticles undergo free radical polymerization, thereby enhancing the toughness and strength of the plastic material. When preparing the modified bio-polyester, diols and dibasic acids are used to esterify and polymerize the bio-polyester, thereby improving the flexibility of the modified bio-polyester. , lowering its glass transition temperature, further improving the strength and toughness of the plastic material, using toluene diisocyanate to end-cap the unsaturated polyester, increasing the molecular weight of the bio-polyester, and further enhancing the cohesive force between the molecular chains, making the plastic material less likely to break or plastically deform under the action of external forces, and the introduced itaconic acid retains the unsaturated bonds during the reaction process, and chemically bonds with the composite nanoparticles during the further preparation of the plastic material, thereby jointly improving the mechanical properties of the plastic material, and compounding the modified bio-polyester with the composite nanoparticles can also improve the environmental performance of the plastic material.
[0056] 2. The nano-reinforced and toughened UV-resistant plastic material of the present invention is prepared by dropping 2-methylene-1,3-dioxepane and methyl acrylate onto esterified cellulose under the initiation of potassium persulfate to form a shell structure of a graft copolymer. Under the action of tensile stress, the local stress concentrated in the esterified cellulose core can be transferred to the soft shell layer through covalent bonds. When cracks are generated in the soft shell, they can be inhibited or terminated by the starch core through covalent bond transfer, which helps to prevent further expansion of the cracks and further improves the toughness and strength of the plastic material. During the polymerization process, ester groups are introduced into 2-methylene-1,3-dioxepane and methyl acrylate in the shell structure, which is beneficial to the movement of molecular chain segments and improves the toughness of the plastic material. In addition, because the shell structure is degradable, the environmental performance of the plastic material is further improved.
[0057] 3. The nano-reinforced and toughened UV-resistant plastic material of the present invention first prepares graphene aerogel by a chemical reduction self-assembly method to provide a three-dimensional conductive network framework for composite nanoparticles, and then adopts a sol-gel method to in-situ generate nano carbon dioxide particles in the graphene aerogel, thereby improving the dispersibility of the composite nanoparticles when preparing the plastic material. The graphene nano-titanium dioxide aerogel after the reaction is completed is then subjected to a microwave irradiation reduction process to make the aerogel sheet layer as a whole fluffy and wrinkled, which is conducive to multiple reflections of ultraviolet rays between layers, thereby improving the UV resistance of the plastic material. In addition, under microwave radiation, the oxygen-containing groups in the aerogel are reduced, the π-π conjugated structure is restored, and the crystal plane spacing between the graphene sheets is reduced, thereby improving the electron migration ability in the aerogel network, improving the conductivity of the composite nanoparticles, and further improving the antistatic performance of the plastic material. DETAILED DESCRIPTION
[0058] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0059] Embodiment 1:
[0060] This embodiment provides a method for preparing a nano-enhanced and toughened UV-resistant plastic material, comprising the following steps:
[0061] S1. Preparation of modified biopolyester:
[0062] Weigh: 100 g of itaconic acid, 150 g of sebacic acid, 5 L of toluene, 5 g of boron trifluoride and 300 g of 1,4-butanediol into a three-necked flask, heat to 120° C., and keep warm for 4 hours. After the reaction is completed, add purified water into the three-necked flask, raise the temperature of the reactor to 120° C., and distill under reduced pressure until no liquid is produced to obtain unsaturated polyester;
[0063] Weigh: 50 g of unsaturated polyester and 1 L of toluene are placed in a three-necked flask and stirred, the amount of toluene diisocyanate is calculated according to half of the molar amount of hydroxyl groups in the unsaturated polyester and added to the three-necked flask, the three-necked flask is heated to 75°C, and the reaction is kept warm for 2 hours. After the reaction is completed, the three-necked flask is cooled to room temperature, filtered, and the filter cake is transferred to a vacuum drying oven at a temperature of 65-75°C, and dried to constant weight to obtain modified bio-polyester.
[0064] S2. Preparation of modified cellulose:
[0065] Weigh: 100 g of hydroxyethyl cellulose, 1.2 L of tetrahydrofuran, 10 g of pyridine, 5 g of acryloyl chloride and 5 g of stearoyl chloride in a three-necked flask protected by nitrogen, heat to 50°C, and keep warm for 2 hours. After the reaction is completed, filter, wash the filter cake with ethanol twice, and dry it in a vacuum drying oven at 45°C to constant weight to obtain esterified cellulose;
[0066] Weigh: 100 g of chloroacetaldehyde dimethyl acetal, 80 g of 1,4-butanediol and 1 g of catalyst, place in a three-necked flask protected by nitrogen atmosphere, heat to 110° C., keep warm for 2 h, filter after the reaction is completed, place the filtrate on a rotary evaporator at 40° C., and evaporate under reduced pressure until no liquid is produced to obtain 2-chloromethyl-1,3-dioxepane;
[0067] Weigh: 17 g of potassium tert-butoxide, 13 g of tert-butanol and 800 mL of N,N-dimethylformamide, put them in a three-necked flask, add 25 g of 2-chloromethyl-1,3-dioxepane dropwise, raise the temperature to 80°C, and keep the temperature to react for 6 hours. After the reaction is completed, add ether to the three-necked flask, raise the temperature to 110°C, and distill under reduced pressure until no liquid is produced to obtain 2-methylene-1,3-dioxepane;
[0068] Weigh: 100 g of esterified cellulose, 20 g of potassium persulfate and 3 L of deionized water, place in a three-necked flask protected by nitrogen atmosphere, heat to 80°C, add 180 g of 2-methylene-1,3-dioxepane and 80 g of methyl acrylate dropwise, after completion, transfer the reaction solution to a rotary evaporator with a water bath temperature of 65°C, and evaporate under reduced pressure until no liquid is extracted to obtain modified cellulose.
[0069] S3. Preparation of composite nanoparticles:
[0070] Weigh: 10 mL of deionized water, 20 mL of ethanol and 1 mL of concentrated hydrochloric acid in a three-necked flask, stir at room temperature for 20 min to obtain a mixed acid solution for later use;
[0071] Weigh: 10 mL of n-butyl titanate, 5 g of vinyl triethoxysilane and 20 mL of ethanol into a three-necked flask, mix well, then drop 5 mL of the mixed acid solution, stir at room temperature for 20 min to obtain a nano-titanium dioxide sol solution for later use;
[0072] Weigh: 10 g of graphene oxide, 15 g of L-ascorbic acid and 200 mL of deionized water in a three-necked flask, heat to 50° C., and ultrasonically disperse for 2 h. After dispersion is completed, place the dispersion in a vacuum drying oven at 70° C. and dry to constant weight to obtain graphene aerogel;
[0073] Under vacuum environment, the graphene aerogel was immersed in nano-titanium dioxide sol solution, left to stand for 2 hours, heated to 50°C, and kept warm for 3 hours. After the reaction was completed, it was washed twice with deionized water, dried, and irradiated with microwaves at a power of 800 W for 1 minute to obtain composite nanoparticles.
[0074] S4. Preparation of plastic materials:
[0075] Stearate, antioxidant 168 and phthalate are mixed uniformly in a weight ratio of 2:1:4 to obtain an auxiliary additive for later use;
[0076] Weigh: 900 g of modified bio-polyester, 100 g of modified cellulose, 150 g of composite nanoparticles, 10 g of dicumyl peroxide and 50 g of auxiliary additives, add them into a twin-screw extruder for melt extrusion, and then inject them into a single-screw granulator to obtain a plastic material.
[0077] Embodiment 2:
[0078] S1. Preparation of modified biopolyester:
[0079] Weigh: 150 g of itaconic acid, 250 g of sebacic acid, 7.5 L of toluene, 5 g of boron trifluoride and 350 g of 1,4-butanediol in a three-necked flask, heat to 125° C., and keep warm for 5 hours. After the reaction is completed, add purified water to the three-necked flask, raise the temperature of the reactor to 125° C., and distill under reduced pressure until no liquid is produced to obtain unsaturated polyester;
[0080] Weigh: 75 g of unsaturated polyester and 1.2 L of toluene are placed in a three-necked flask and stirred, the amount of toluene diisocyanate is calculated according to half of the molar amount of hydroxyl groups in the unsaturated polyester and added to the three-necked flask, the three-necked flask is heated to 80°C, and the reaction is kept warm for 2.5 hours. After the reaction is completed, the three-necked flask is cooled to room temperature, filtered, and the filter cake is transferred to a vacuum drying oven at a temperature of 65-75°C and dried to constant weight to obtain modified bio-polyester.
[0081] S2. Preparation of modified cellulose:
[0082] Weigh: 125 g of hydroxyethyl cellulose, 1.2 L of tetrahydrofuran, 12.5 g of pyridine, 7.5 g of acryloyl chloride and 7.5 g of stearoyl chloride in a three-necked flask protected by nitrogen, heat to 55°C, and keep warm for 2.5 hours. After the reaction is completed, filter, wash the filter cake with ethanol twice, and dry it in a vacuum drying oven at 50°C to constant weight to obtain esterified cellulose;
[0083] Weigh: 110 g of chloroacetaldehyde dimethyl acetal, 90 g of 1,4-butanediol and 1.5 g of catalyst, place in a three-necked flask protected by nitrogen atmosphere, heat to 115° C., keep warm for 2 h, filter after the reaction is completed, place the filtrate on a rotary evaporator at a temperature of 45° C., and evaporate under reduced pressure until no liquid is produced to obtain 2-chloromethyl-1,3-dioxaheptane;
[0084] Weigh: 18 g of potassium tert-butoxide, 14 g of tert-butanol and 900 mL of N,N-dimethylformamide, put them in a three-necked flask, add 27 g of 2-chloromethyl-1,3-dioxepane dropwise, raise the temperature to 100°C, and keep the temperature to react for 6.5 hours. After the reaction is completed, add ether to the three-necked flask, raise the temperature to 115°C, and distill under reduced pressure until no liquid is produced to obtain 2-methylene-1,3-dioxepane;
[0085] Weigh: 125 g of esterified cellulose, 25 g of potassium persulfate and 4 L of deionized water, place in a three-necked flask protected by a nitrogen atmosphere, heat to 90°C, add dropwise 190 g of 2-methylene-1,3-dioxepane and 85 g of methyl acrylate. After completion, transfer the reaction solution to a rotary evaporator with a water bath temperature of 70°C, and evaporate under reduced pressure until no liquid is extracted to obtain modified cellulose.
[0086] S3. Preparation of composite nanoparticles:
[0087] Weigh: 15 mL of deionized water, 30 mL of ethanol and 1.5 mL of concentrated hydrochloric acid in a three-necked flask, stir at room temperature for 250 min to obtain a mixed acid solution for later use;
[0088] Weigh: 15 mL of n-butyl titanate, 7.5 g of vinyl triethoxysilane and 30 mL of ethanol into a three-necked flask, mix well, then drop 7.5 mL of the mixed acid solution, stir at room temperature for 25 min to obtain a nano-titanium dioxide sol solution for later use;
[0089] Weigh: 15 g of graphene oxide, 20 g of L-ascorbic acid and 350 mL of deionized water in a three-necked flask, heat to 55° C., and ultrasonically disperse for 2.5 h. After dispersion is completed, place the dispersion in a vacuum drying oven at 75° C. and dry to constant weight to obtain graphene aerogel;
[0090] Under vacuum environment, the graphene aerogel was immersed in nano-titanium dioxide sol solution, left to stand for 2 hours, heated to 55°C, and kept warm for 4 hours. After the reaction was completed, it was washed twice with deionized water, dried, and irradiated with microwaves at a power of 800 W for 2 minutes to obtain composite nanoparticles.
[0091] S4. Preparation of plastic materials:
[0092] Stearate, antioxidant 168 and phthalate are mixed uniformly in a weight ratio of 2:1:4 to obtain an auxiliary additive for later use;
[0093] Weigh: 950 g of modified bio-polyester, 125 g of modified cellulose, 175 g of composite nanoparticles, 12.5 g of dicumyl peroxide and 70 g of auxiliary additives, add them into a twin-screw extruder for melt extrusion, and then inject them into a single-screw granulator to obtain a plastic material.
[0094] Embodiment 3:
[0095] S1. Preparation of modified biopolyester:
[0096] Weigh: 200 g of itaconic acid, 320 g of sebacic acid, 10 L of toluene, 5 g of boron trifluoride and 400 g of 1,4-butanediol in a three-necked flask, heat to 130° C., and keep warm for 6 hours. After the reaction is completed, add purified water to the three-necked flask, raise the temperature of the reactor to 130° C., and distill under reduced pressure until no liquid is produced to obtain unsaturated polyester;
[0097] Weigh: 100 g of unsaturated polyester and 1.5 L of toluene are placed in a three-necked flask and stirred, the amount of toluene diisocyanate is calculated according to half of the molar amount of hydroxyl groups in the unsaturated polyester and added to the three-necked flask, the three-necked flask is heated to 85° C., and the reaction is kept warm for 3 hours. After the reaction is completed, the three-necked flask is cooled to room temperature, filtered, and the filter cake is transferred to a vacuum drying oven at a temperature of 65-75° C. and dried to constant weight to obtain modified bio-polyester.
[0098] S2. Preparation of modified cellulose:
[0099] Weigh: 150 g of hydroxyethyl cellulose, 1.3 L of tetrahydrofuran, 15 g of pyridine, 10 g of acryloyl chloride and 10 g of stearoyl chloride in a three-necked flask protected by nitrogen, heat to 60°C, and keep warm for 3 hours. After the reaction is completed, filter, wash the filter cake with ethanol twice, and dry it in a vacuum drying oven at 55°C to constant weight to obtain esterified cellulose;
[0100] Weigh: 120 g of chloroacetaldehyde dimethyl acetal, 100 g of 1,4-butanediol and 2 g of catalyst, place in a three-necked flask protected by nitrogen atmosphere, heat to 120° C., keep warm for 2 h, filter after the reaction is completed, place the filtrate on a rotary evaporator at a temperature of 45° C., and evaporate under reduced pressure until no liquid is produced to obtain 2-chloromethyl-1,3-dioxepane;
[0101] Weigh: 20 g of potassium tert-butoxide, 15 g of tert-butanol and 1 L of N,N-dimethylformamide in a three-necked flask, dropwise add 30 g of 2-chloromethyl-1,3-dioxepane, raise the temperature to 115°C, and keep the temperature for reaction for 7 hours. After the reaction is completed, add ether to the three-necked flask, raise the temperature to 120°C, and distill under reduced pressure until no liquid is produced to obtain 2-methylene-1,3-dioxepane;
[0102] Weigh: 150 g of esterified cellulose, 30 g of potassium persulfate and 5 L of deionized water, place in a three-necked flask protected by nitrogen atmosphere, heat to 100 ° C, add 200 g of 2-methylene-1,3-dioxepane and 90 g of methyl acrylate dropwise, after completion, transfer the reaction solution to a rotary evaporator with a water bath temperature of 75 ° C, and evaporate under reduced pressure until no liquid is extracted to obtain modified cellulose.
[0103] S3. Preparation of composite nanoparticles:
[0104] Weigh: 20 mL of deionized water, 40 mL of ethanol and 2 mL of concentrated hydrochloric acid in a three-necked flask, stir at room temperature for 30 min to obtain a mixed acid solution for later use;
[0105] Weigh: 20 mL of n-butyl titanate, 10 g of vinyl triethoxysilane and 40 mL of ethanol into a three-necked flask, mix well, then drop 10 mL of the mixed acid solution, stir at room temperature for 30 min to obtain a nano-titanium dioxide sol solution for later use;
[0106] Weigh: 20 g of graphene oxide, 30 g of L-ascorbic acid and 500 mL of deionized water in a three-necked flask, heat to 60° C., and ultrasonically disperse for 3 h. After dispersion is completed, place the dispersion in a vacuum drying oven at 80° C. and dry to constant weight to obtain graphene aerogel;
[0107] Under vacuum environment, the graphene aerogel was immersed in nano-titanium dioxide sol solution, left to stand for 2 hours, heated to 60°C, and kept warm for 4 hours. After the reaction was completed, it was washed twice with deionized water, dried, and irradiated with microwaves at a power of 800 W for 2 minutes to obtain composite nanoparticles.
[0108] S4. Preparation of plastic materials:
[0109] Stearate, antioxidant 168 and phthalate are mixed uniformly in a weight ratio of 2:1:4 to obtain an auxiliary additive for later use;
[0110] Weigh: 1000 g of modified bio-polyester, 150 g of modified cellulose, 200 g of composite nanoparticles, 15 g of dicumyl peroxide and 80 g of auxiliary additives, add them into a twin-screw extruder for melt extrusion, and then inject them into a single-screw granulator to obtain a plastic material.
[0111] Comparative Example 1:
[0112] The difference between this comparative example and Example 3 is that step S1 is eliminated, and the unsaturated polyester in step S1 replaces the modified biopolyester in step S4.
[0113] Comparative Example 2:
[0114] The difference between this comparative example and Example 3 is that step S2 is omitted and modified cellulose is not added in step S4.
[0115] Comparative Example 3:
[0116] The difference between this comparative example and Example 3 is that no graphene aerogel is added in step S3.
[0117] Performance Testing:
[0118] The elongation at break and tensile strength of the plastic material samples prepared in Examples 1-3 and Comparative Examples 1-3 were tested respectively with reference to the standard GB / T 10654-2001 "Determination of tensile strength and elongation at break of polymer porous elastic materials";
[0119] The shear strength of the plastic material samples prepared in Examples 1-3 and Comparative Examples 1-3 were tested respectively with reference to the standard HG / T 3839-2006 "Plastic Shear Strength Test Method - Perforation Method";
[0120] The resistivity of the plastic material samples prepared in Examples 1-3 and Comparative Examples 1-3 was tested respectively with reference to the standard GB / T 15662-1995 "Test method for volume resistivity of conductive and antistatic plastics";
[0121] Referring to the standard GB / T 16422.1-2019 "Plastic Laboratory Light Source Exposure Test Method Part 1: General Principles", the shear strength and tensile strength of the plastic material samples prepared in Examples 1-3 and Comparative Examples 1-3 were tested under laboratory simulated ultraviolet light irradiation. The specific test results are shown in Table 1 below - Physical properties test data table of each sample;
[0122] Referring to the standard GB / T 41010-2021 "Degradation performance and labeling requirements of biodegradable plastics and products", the 12-week disintegration rate and 180-day biodegradation rate of the plastic material samples prepared in Examples 1-3 and Comparative Examples 1-3 were respectively measured under industrial composting conditions. The specific test results are shown in Table 2 below - Biodegradation performance test data table of the samples.
[0123] Table 1- Physical properties test data of each sample:
[0124] ;
[0125] Table 2-Biodegradation performance test data of samples:
[0126] ;
[0127] Data Analysis:
[0128] The data in Table 1 above are compared and analyzed. The tensile elongation at break of the nano-enhanced toughened UV-resistant plastic material prepared by the present invention is 361%, the tensile strength is 45.2 MPa, the shear strength is 37.5 MPa, the resistivity is 37.5 Ω·m, the tensile strength after simulated UV lamp irradiation is 42.3 MPa, and the shear strength after simulated UV lamp irradiation is 32.6 MPa. The prepared plastic material sample has a 12-week disintegration rate of 93.2% under industrial composting conditions, and a 180-day biodegradability rate of 93.4%, and all data are better than the comparative example;
[0129] Data description:
[0130] By comparing the data of Example 3 and Comparative Example 1, it is found that when preparing the modified bio-polyester, the bio-polyester is introduced by esterification and polymerization with diols and dibasic acids, which improves the flexibility of the modified bio-polyester, can reduce its glass transition temperature, and further improves the elongation at break, tensile strength and shear strength of the plastic material. In addition, the introduced itaconic acid retains unsaturated bonds during the reaction process, and chemically bonds with the composite nanoparticles when further preparing the plastic material, thereby jointly improving the elongation at break, tensile strength and shear strength of the plastic material. The modified bio-polyester is compounded with the composite nanoparticles, which can also improve the environmental performance of the plastic material.
[0131] By comparing the data of Example 3 and Comparative Example 2, it is found that under the initiation of potassium persulfate, 2-methylene-1,3-dioxepane and methyl acrylate are added dropwise to the esterified cellulose to form a shell structure of the graft copolymer, which improves the elongation at break, tensile strength and shear strength of the plastic material, and because the shell structure is degradable, the environmental performance of the plastic material is further improved;
[0132] By comparing the data of Example 3 and Comparative Example 3, it is found that the graphene aerogel is prepared by the chemical reduction self-assembly method, which provides a three-dimensional conductive network framework for the composite nanoparticles and reduces the resistivity of the plastic material. Then, the sol-gel method is used to in-situ generate nano carbon dioxide particles in the graphene aerogel, which improves the dispersibility of the composite nanoparticles when preparing the plastic material. Then, the graphene nano-titanium dioxide aerogel after the reaction is completed is subjected to microwave irradiation reduction treatment, so that the aerogel sheet becomes fluffy and wrinkled as a whole, which is conducive to multiple reflections of ultraviolet rays between layers, and improves the anti-ultraviolet performance of the plastic material. In addition, under microwave radiation, the oxygen-containing groups in the aerogel are reduced, the π-π conjugated structure is restored, and the crystal plane spacing between the graphene sheets is reduced, so that the electron migration ability in the aerogel network is reduced, the resistivity of the plastic material is reduced, and the antistatic performance of the plastic material is further improved.
[0133] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A method for preparing a nano-reinforced and toughened UV-resistant plastic material, characterized in that: The following steps are involved: S1. Place itaconic acid, sebacic acid, toluene, boron trifluoride and 1,4-butanediol in a three-necked flask, heat to 120-130° C., keep warm for 4-6 hours, and post-treat to obtain unsaturated polyester; S2, placing unsaturated polyester, toluene and toluene diisocyanate in a three-necked flask, heating to 75-85° C., keeping the temperature for reaction for 2-3 hours, and post-treating to obtain modified bio-polyester; S3, adding the modified bio-polyester, modified cellulose, composite nanoparticles, dicumyl peroxide and auxiliary additives into a twin-screw extruder for melt extrusion, and then injecting into a single-screw granulator to obtain a plastic material.
2. The method for preparing a nano-reinforced and toughened UV-resistant plastic material according to claim 1, characterized in that: In step S1, the dosage ratio of itaconic acid, sebacic acid, toluene, boron trifluoride and 1,4-butanediol is 100-200g:150-320g:5-10L:5g:300-400g; in step S2, the dosage ratio of the unsaturated polyester and toluene is 50-100g:1-1.5L, and the molar ratio of toluene diisocyanate is half of the molar amount of hydroxyl groups in the unsaturated polyester; in step S3, the auxiliary additive is a dispersant , antioxidant, and plasticizer are composed in a weight ratio of 2:1:4, the dispersant is stearate, the antioxidant is one or more of antioxidant 168, antioxidant 364, and antioxidant 1010, the plasticizer is phthalate, and the dosage ratio of the modified bio-polyester, modified cellulose, composite nanoparticles, diisopropyl peroxide and auxiliary additives is 900-1000g:100-150g:150-200g:10-15g:50-80g.
3. The method for preparing a nano-reinforced and toughened UV-resistant plastic material according to claim 1, characterized in that: The method for preparing the modified cellulose comprises the following steps: A1. Under the protection of inert gas, hydroxyethyl cellulose, tetrahydrofuran, pyridine, acryloyl chloride and stearoyl chloride are placed in a three-necked flask, the temperature is raised to 50-60°C, the temperature is kept for reaction for 2-3 hours, and the esterified cellulose is obtained by post-treatment; A2. Under nitrogen atmosphere, esterified cellulose, potassium persulfate and deionized water are placed in a three-necked flask, heated to 80-100° C., 2-methylene-1,3-dioxepane and methyl acrylate are added dropwise, and modified cellulose is obtained by post-treatment.
4. The method for preparing a nano-reinforced and toughened UV-resistant plastic material according to claim 3, characterized in that: In step A1, the amount ratio of hydroxyethyl cellulose, tetrahydrofuran, pyridine, acryloyl chloride and stearoyl chloride is 100-150g:1.2-1.3L:10-15g:5-10g:5-10g; in step A2, the amount ratio of esterified cellulose, potassium persulfate, deionized water, 2-methylene-1,3-dioxepane and methyl acrylate is 100-150g:20-30g:3-5L:180-200g:80-90g.
5. The method for preparing a nano-reinforced and toughened UV-resistant plastic material according to claim 3, characterized in that: The preparation method of 2-methylene-1,3-dioxepane comprises the following steps: B1. Under a nitrogen atmosphere, place chloroacetaldehyde dimethyl acetal, 1,4-butanediol and a catalyst in a three-necked flask, heat to 110-120°C, keep warm for 1-2h, and post-treat to obtain 2-chloromethyl-1,3-dioxepane; B2. Place potassium tert-butoxide, tert-butanol and N,N-dimethylformamide in a three-necked flask, add 2-chloromethyl-1,3-dioxepane dropwise, raise the temperature to 80-115°C, keep the temperature for 6-7h, and post-treat to obtain 2-methylene-1,3-dioxepane.
6. The method for preparing a nano-reinforced and toughened UV-resistant plastic material according to claim 5, characterized in that: In step B1, the catalyst is an acidic cation exchange resin Dowex 50 H+ type, and the amount ratio of the chloroacetaldehyde dimethyl acetal, 1,4-butanediol and the catalyst is 100-120g:80-100g:1-2g; in step B2, the amount ratio of the potassium tert-butoxide, tert-butanol, N,N-dimethylformamide and 2-chloromethyl-1,3-dioxepane is 17-20g:13-15g:800-1000mL:25-30g.
7. The method for preparing a nano-reinforced and toughened UV-resistant plastic material according to claim 1, characterized in that: The method for preparing the composite nanoparticles comprises the following steps: C1. Place deionized water, ethanol and concentrated hydrochloric acid in a three-necked flask and stir at room temperature for 20-30 minutes to obtain a mixed acid solution for later use; C2, put n-butyl titanate, vinyl triethoxysilane and ethanol in a three-necked flask, mix them evenly, add the mixed acid solution dropwise, stir at room temperature for 20-30 minutes, and obtain a nano titanium dioxide sol solution for standby use; C3. Under vacuum environment, immerse the graphene aerogel in nano-titanium dioxide sol solution, let it stand for 1-2 hours, heat it to 50-60°C, keep it warm for 3-4 hours, and then post-treat it to obtain composite nanoparticles.
8. The method for preparing a nano-reinforced and toughened UV-resistant plastic material according to claim 7, characterized in that: In step C1, the volume ratio of deionized water, ethanol and concentrated hydrochloric acid is 10-20:20-40:1-2; in step C2, the amount ratio of n-butyl titanate, vinyltriethoxysilane, ethanol and mixed acid solution is 10-20mL:5-10g:20-40mL:5-10mL.
9. The method for preparing a nano-reinforced and toughened UV-resistant plastic material according to claim 7, characterized in that: The preparation method of the graphene aerogel is as follows: graphene oxide, L-ascorbic acid and deionized water are placed in a three-necked flask, heated to 50-60° C., ultrasonically dispersed for 2-3 hours, and post-treated to obtain the graphene aerogel.
10. The method for preparing a nano-reinforced and toughened UV-resistant plastic material according to claim 9, characterized in that: The usage ratio of the graphene oxide, L-ascorbic acid and deionized water is 10-20 g:15-30 g:200-500 mL.
Citation Information
Patent Citations
Ultrasonic microwave synthesis method for poly(butanediol itaconate-co-butanediol sebate)copolyester
CN105601894A
High-strength wear-resistant composite plastic with high auxiliary material content and preparation method of high-strength wear-resistant composite plastic
CN119192753A
Preparation method for montmorillonite-magnesium hydroxide composite microencapsulated flame retardant
WO2022068065A1